Old forts of Southern Colorado. - Beckner, Raymond M. frey50 (Canyon City, CO. Raymond M. Beckner, 1975)
Brief histories of numerous old forts in the southern half of Colorado.
#6
Keywords: New Mexico - Northeastern New Mexico and Southeastern Colorado -- Old forts - History. -- Southern Colorado - History